Vancomycin‐Mediated Binding of DNA Origami Nanostructures to Gram‐Positive and Gram‐Negative Bacteria - Coşkuner Leineweber, Özge; Hofmann, Ulrike; Grundmeier, Guido; Zhang, Yixin; Keller, Adrian Clemens (ChemBioChem)
DNA origami nanostructures (DONs) have promising applications in biomedicine and biosensing, which often require their efficient binding to target cells. By immobilizing the glycopeptide antibiotic vancomycin on DONs, DON binding to Gram‐positive and Gram‐negative bacteria can be facilitated. Here, we investigate how this multivalent binding is affected by the number and arrangement of the vancomycin modifications on two‐dimensional DONs. We find that for both Gram‐positive Bacillus subtilis and Gram‐negative Escherichia coli , binding increases with the number of vancomycin modifications per DON. In general, binding to E. coli is stronger than to B. subtilis , which may be attributed to differences in the architectures of the cell envelopes. Interestingly, for both bacteria, the total number of vancomycin modifications appears to be more important than their arrangement, as DONs with 18 vancomycin molecules on one side show similar binding as DONs with 18 vancomycin molecules distributed over both sides. This enables the attachment of multiple probe molecules to the vancomycin‐free side of the DONs for enhancing detection efficiency without compromising binding affinity. These results may thus provide guidelines for the design and synthesis of vancomycin‐modified DONs for antimicrobial drug delivery and pathogen detection.

Effect of DNA Origami Nanostructures on Bacterial Growth - Garcia-Diosa, Jaime Andres; Grundmeier, Guido; Keller, Adrian (ChemBioChem)
DNA origami nanostructures are a powerful tool in biomedicine and can be used to combat drug‐resistant bacterial infections. However, the effect of unmodified DNA origami nanostructures on bacteria is yet to be elucidated. With the aim to obtain a better understanding of this phenomenon, the effect of three DNA origami shapes, i.e., DNA origami triangles, six‐helix bundles (6HBs), and 24‐helix bundles (24HBs), on the growth of Gram‐negative Escherichia coli and Gram‐positive Bacillus subtilis is investigated. These results reveal that while triangles and 24HBs can be used as a source of nutrients by E. coli and thereby promote population growth, their effect is much smaller than that of genomic single‐ and double‐stranded DNA. However, no effect on E. coli population growth is observed for the 6HBs. On the other hand, B. subtilis does not show any significant changes in population growth when cultured with the different DNA origami shapes or genomic DNA. The detailed effect of DNA origami nanostructures on bacterial growth thus depends on the competence signals and uptake mechanism of each bacterial species, as well as the DNA origami shape. This should be considered in the development of antimicrobial DNA origami nanostructures.
Keywords: Organic Chemistry; Molecular Biology; Molecular Medicine; Biochemistry

Effect of Ionic Strength on the Thermal Stability of DNA Origami Nanostructures - Hanke, Marcel; Tomm, Emilia; Grundmeier, Guido; Keller, Adrian (ChemBioChem)
Keywords: Organic Chemistry; Molecular Biology; Molecular Medicine; Biochemistry

Real-Time Observation of Superstructure-Dependent DNA Origami Digestion by DNase I Using High-Speed Atomic Force Microscopy. - Ramakrishnan, S; Shen, B; Kostiainen, MA; Grundmeier, Guido; Keller, Adrian; Linko, V (ChemBioChem)